2014
DOI: 10.1097/hjh.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor XIIa-kinin-mediated contribution to hypertension of chronic kidney disease

Abstract: FXIIa-kininogen mediated vasoconstriction contributes significantly to CKD hypertension in Brown Norway rats; this novel mechanism may be active in humans with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Among these genes, CRIP1 , MYADM , TIPARP , F12 , and TSC22D3 have been previously implicated in hypertension. 15,19,3335 For the other transcripts, a connection to diseases related to BP, such as obesity and CVD, as well as important roles in the immune system have been described, 36 but the association with BP traits is novel. These findings seem plausible because numerous studies suggest that hypertension represents an inflammatory state and an involvement of the immune system and, in particular, monocytes in the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, CRIP1 , MYADM , TIPARP , F12 , and TSC22D3 have been previously implicated in hypertension. 15,19,3335 For the other transcripts, a connection to diseases related to BP, such as obesity and CVD, as well as important roles in the immune system have been described, 36 but the association with BP traits is novel. These findings seem plausible because numerous studies suggest that hypertension represents an inflammatory state and an involvement of the immune system and, in particular, monocytes in the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“… No Francois et al 74 2020 In vivo Does routine hemodialysis increase FXII, FXI, or PK activation compared to baseline levels or compared to control participants? No Papageorgiou et al 75 2014 In vivo Is FXIIa higher in patients with ESKD receiving long-term hemodialysis compared with healthy controls? Yes Hong et al 76 2001 Ex vivo Does FXIIa play a role in thrombin generation when whole blood is incubated with PVC?…”
Section: Contact Activation In Hemodialysismentioning
confidence: 99%
“… 74 On the other hand, an additional study showed that FXIIa was 3 times higher in patients with ESKD receiving long-term hemodialysis compared with healthy controls. 75 The contradictory findings of these studies could be attributed to the differing populations, the small sample sizes, or the difficulties associated with measuring contact activation in vivo, including the sensitivity of different laboratory markers as well as the potential for artifactual (ex vivo) activation of FXII after blood has been drawn.…”
Section: Contact Activation In Hemodialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Kallikrein is derived from the blood plasma or tissue and formed from conversion of prokallikrein by factor XIIa, which is activated in the blood coagulation process. Kallikrein is a serine protease that cleaves kininogen to release vasoactive kinins and activates factor XIIa (positive feedback) (Clermont et al, 2011;Papageorgiou et al, 2014).…”
Section: Kallikreinmentioning
confidence: 99%